2001
DOI: 10.3310/hta5220
|View full text |Cite
|
Sign up to set email alerts
|

The measurement and monitoring of surgical adverse events

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
217
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(226 citation statements)
references
References 227 publications
(427 reference statements)
3
217
0
6
Order By: Relevance
“…Since the 1990s, increasing interest has been placed in the incorporation of clinical adverse events as quality indicators in hospital quality assurance programs [5] . Adverse postoperative events, and very specially SSI rates after specific procedures, gained popularity as hospital quality indicators in the 1980s [13,14] , and are currently some of the most widely used hospital quality indicators worldwide [5,[15][16][17] .…”
Section: Rates Of Ssi As Quality Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the 1990s, increasing interest has been placed in the incorporation of clinical adverse events as quality indicators in hospital quality assurance programs [5] . Adverse postoperative events, and very specially SSI rates after specific procedures, gained popularity as hospital quality indicators in the 1980s [13,14] , and are currently some of the most widely used hospital quality indicators worldwide [5,[15][16][17] .…”
Section: Rates Of Ssi As Quality Indicatorsmentioning
confidence: 99%
“…Since the 1990s, increasing interest has been placed in the incorporation of clinical adverse events as quality indicators in hospital quality assurance programs [5] . Adverse postoperative events, and very specially SSI rates after specific procedures, gained popularity as hospital quality indicators in the 1980s [13,14] , and are currently some of the most widely used hospital quality indicators worldwide [5,[15][16][17] . Other outcomes or processes frequently proposed as measures of quality in surgical care include postoperative mortality, postoperative long-term survival, postoperative functional status and health-related quality of life, other postoperative morbidity (e.g.…”
Section: Rates Of Ssi As Quality Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of surgical adverse events in 2001 found 41 different definitions and 13 grading scales for surgical-site infections among the 82 studies included in the review. 30 The recent debate regarding definitions of perioperative myocardial injury is likewise ongoing. 31,32 Even seemingly simple binary constructs such as mortality may be presented in a variety of ways.…”
Section: Clinician-described or Patient-reportedmentioning
confidence: 99%